Community Understanding of the Obligation to Pay Zakat Mal in Sungai Mengkuang Hamlet, Bungo Regency - Busriadi, Busriadi; Sopriyanto, Sopriyanto (Rangkiang: Journal of Islamic Economics and Business, 2025)
This research focuses on the community's understanding of the obligation to pay zakat mal in Sungai Mengkuang Hamlet, Bungo Regency. The type of research used in this study is qualitative research with a descriptive approach. The authors employed field research methodology, directly visiting the community in Sungai Mengkuang Hamlet, Bungo Regency. Based on the research findings, it can be concluded that there is a significant disparity in understanding regarding the obligation to pay zakat mal. Some members of the community demonstrate comprehensive understanding and can accurately explain the concept of zakat mal. However, others still have misconceptions or are not even clearly familiar with zakat mal. The practice of zakat mal in Sungai Mengkuang Hamlet is influenced by a convergence of dynamically interacting factors. Solid religious understanding that still requires deepening, strong social support from family and community, ease of access through digital technology, and economic realities that demand flexibility all contribute to shaping the community's zakat behavior.